Development of an "A" genome-specific sequence characterised amplified region (SCAR) marker in Musa L. (bananas and plantains) - Mabonga, Lloyd (Vaal University of Technology, 2014)
Most cultivated bananas and plantains (Musa spp. sect. Eumusa), originated from two wild diploid species, Musa acuminata Colla (AA) and Musa balbisiana Colla (BB), which contributed the A and B genomes, respectively. The two genomes confer different traits to a banana plant. Intra- and interspecific hybridization between the wild diploid species, somatic mutations and selection over many thousands of years has given rise to considerable genetic variability in cultivated bananas. Bananas are classified according to its genome composition and a number of morphological traits are used to identify the genomes of a plant. Morphological classification can be misleading since the morphology of plants can be affected by environmental factors. Molecular techniques to identify the genomes of banana have many advantages. The objective of this study was to develop a SCAR (sequence characterized amplified region) marker from a previously reported A genome-specific RAPD fragment that distinguish the A genome of banana from the B genome. This fragment designated OPA17600 was cloned, sequenced and used to design longer 20-mer SCAR primers. Verification of the SCAR primers for its fidelity to the A genome was carried out on a sample of 22 homo-and heterogenomic accessions representing landraces and hybrids of different ploidy and genome combinations. Out of six primers sets that were tested one set (SC3) produced a unique 600 bp in all the A genome containing banana accessions. However, these primers also amplified an 800 bp fragment in all the BB genotypes and some accessions containing the A and B genomes. While previous reports suggested that there was considerable differentiation between the A and B genomes, recent evidence points to the contrary. The presence of the A genome fragment in the B genome genotypes and accessions may be due to recombination between the two genomes, translocations and substitutions. The study concluded that the 600-bp SCAR sequence is conserved across the A genome in Musa and can be used to identify the A genome in banana classification and Musa breeding programmes.
M. Tech. (Department of Biosciences, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Bananas; Genomes; Banana hybridization; Morphology of plants; Sequence Characterized amplified region marker; Musa breeding programmes; 584.39; Plant genomes.; Plant genetics.; Bananas -- Genetics.; Dissertations, Academic -- South Africa.